Fake news, information at the center of contemporary society: from the educomunicative look - Paletta, Francisco Carlos; Bento, Viviane Patricia (Cadernos de Educação Tecnologia e Sociedade, 2021)
With the large volume of production and dissemination of information in cyberspace, individuals have difficulty in selecting content and end up contributing to the dissemination of false news called: fake news. In this context, media literacy from the point of view of Educommunication is necessary to deal with Information and Communication Technologies (ICT) and to combat the undue spread of false news. The objective of this study is to show how fake news proliferate in the networks and how harmful they can be, as well as to show how Educommunication can be a way for subjects to be able to make a reflective reading about the media they use.